Pengaruh Kualitas Produk, Citra Merek, Dan Harga Terhadap Keputusan Pembelian Jersey Arema Fc Official Store (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2019) - Hilya Salsabila; Abdul Kodir Djaelani; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Football is one of the sports that is very concerned about and favored by people from various parts of the world. One of them is the football club Arema FC.PT. The Indonesian League applies regulations to all clubs that join the IndonesiaSuper League (ISL). Clubs are forced to seek funding professionally and independently, this has made clubs in Indonesia try to hook fans or fanatical football supporters by making them one of the marketing objects. Arema FC is known for its club base with many supporters who are commonly called Aremania.The existence of aremania is a positive side to boosting the club's finances by sellingvarious kinds of merchandise such as club jerseys. This research is to find out andanalyze product quality, brand image and price on purchasing decisions for AremaFC jersey. The population in this study were students of the 2019 Faculty of Economics and Business, Islamic University of Malang. The sampling technique uses purposive sampling which is a sample collection technique based on certain criteria with 80 respondents. The analysis technique uses multiple linear regression analysis. The results of this study indicate that product quality (X1), brand image (X2) and price (X3) have a contribution to the purchasing decision variable by 56%and the remaining 44% is explained by other independent variables that are not present in the study. And simultaneously and partially product quality, brand imageand price have a significant effect on purchasing decisions. Keywords: Product Quality, Brand Image, Price, Purchasing Decisions